(untitled) (Nepal Journal of Epidemiology, 2011)
Nowadays the output—and rewards—of research are based almost entirely on published papers in scientific journals. Scientists in low-income and middle-income settings would like to conduct research for their populations according to their own concerns. They want to be in the frontlines of national and global communications about their country’s experiences. I recommend that properly trained clinical trial experts from developed countries should conduct some workshops on the design, conduct and ethical issues in clinical trials to terminate the research misconduct in developing countries. DOI: http://dx.doi.org/10.3126/nje.v1i2.5090 Nepal Journal of Epidemiology 2011;1 (2):44-46